The Effect of Giving Maggot Mix Flour (Hermetia Illuciens Linnaeus) on Commercial Feed on Growth Weight Mice (Mus Musculus) - Dyanovita Al Kurnia; Arif Aria Hertanto; Wardoyo Wardoyo; Nuril Badriyah; Wahyuni Wahyuni (UNIVERSITAS ISLAM LAMONGAN, 2021)
The study aimed to determine the effect of daily body weight gain (PBBH) in mice given feed containing commercial feed mix maggot flour. The material used in the study was 60 mice that were not differentiated by gender. The study used a completely randomized design (CRD) with unidirectional pattern. The provision of maggot flour in commercial feed was divided into four types of treatment. Each treatment level received three replications, with each replication consisting of 5 mice. If there was an influence on the treatment, the Duncan Multiple Range Test was performed. The followings were the treatments used in the study: P0: 100% commercial feed without maggot flour, P1: commercial feed 95% + 5% maggot flour, P2: commercial feed 90% + 10% maggot flour, P3: commercial feed 85% + 15% maggot flour. The research lasted for approximately 30 days, starting from September 4 to October 6, 2020, at the Basic Laboratory of the Faculty of Animal Husbandry, Islamic University of Lamongan. The results showed a significant effect between treatments (P <0.05) and (P <0.01). The best treatment resulted in the increase of daily body weight gain (PBBH) was P1 (0.35 gr / head / day ± 0.10), P0 (0.29 gr / head / day ± 0.05), P3 (0.20 gr / head / day ± 0.08) , P2 (0.10 gr / head / day ± 0.05). This study concludes that the application of mixed maggot flour as feed to the growth of mice's body weight is the addition of 95% of commercial feed and 5% of maggot flour.